The Epidemiology of Primary Central Nervous System Tumors at the National Neurologic Institute in Saudi Arabia: A Ten-Year Single-Institution Study. (15th February 2020) - Almutrafi, Amna; Bashawry, Yara; AlShakweer, Wafaa; Al-Harbi, Musa; Altwairgi, Abdullah; Al-Dandan, Sadeq
Abstract : Objectives . This study is aimed at describing the epidemiological trends of primary CNS tumors in children and adults at the National Neurologic Institute in Saudi Arabia. Methods . A retrospective epidemiological approach was used where data was obtained from the department of pathology registry files and pathology reports. The records of all patients registered from January 2005 to December 2014 with a diagnosis of primary CNS tumor (brain and spinal cord) were selected. Data about sex, age, tumor location, and histologic type were collected. The classification was based on the International Classification of Diseases for Oncology, 3rd Edition (ICD-O-3). Results . Nine hundred and ninety-two (992) cases of primary CNS tumors throughout the ten years (2005 to 2014) were reviewed. There were 714 (71.97%) adults and 278 (28.02%) in the pediatric age group. Nonmalignant tumors dominated the adult population (60.08%) while malignant tumors were more frequent in the pediatric population. Gliomas constituted the most common neoplastic category in children and adults. The most common single tumor entity was meningioma (26.99%, ICD-O-3 histology codes 9530/0, 9539/1, and 9530/3). Medulloblastomas (ICD-O-3 histology codes 9470, 9471, and 9474) were the most common single tumor entity in the pediatric age group (26.62%). Conclusions . This is an institution-based, detailed, and descriptive epidemiological study of patients with primary CNS tumors in Saudi Arabia. In contrast to other regional and international studies, the medulloblastomas in our institution are more frequent than pilocytic astrocytomas. Limitations to our study included the referral bias and histology-based methodology.